(untitled) (International Journal of Environmental Sciences, 2025)
Fueled by the allure of multibagger stocks exhibiting explosive growth potential, investors continuously explore diverse investment strategies. The quest for profitable trading strategies has led to the development of diverse technical analysis tools. One such approach, the Darvas Box Theory, championed by Nicolas Darvas, emphasizes the identification of breakout opportunities through the analysis of price ranges and volume confirmation. This paper delves into the core principles of the Darvas Box Theory, critically analyzing its strengths and applicability in the dynamic environment of contemporary stock markets in isolating potential multibagger stocks in today’s market environment. The research revisits the Darvas Box Theory’s effectiveness in identifying potential investment opportunities within the Nifty Midcap 50 stocks. Qualitative approach is employed analyzing technical charts obtained from the Trading View platform. The methodology involves manually examining monthly charts to identify Darvas Box formations and then tracking subsequent price movements to assess if these breakouts align with broader market trends. Findings indicate the Darvas Box theory’s efficacy in identifying multibagger stocks and pinpointing opportune entry points for investment purchases. Analysis of Nifty Midcap 50 stocks reveals significant returns, with some stocks exhibiting quadruple-digit growth percentages. The overall return generated by the Darvas Box breakout theory in these stocks is remarkable. In conclusion, this study provides compelling evidence for the utility of the Darvas Box theory in streamlining stock selection and entry timing. The conclusions drawn from this research will serve both academic audiences and practicing investors interested in refining their investment strategies and contribute valuable insights to the field of technical analysis.